Dampak serat terhadap produksi asam lemak rantai pendek pada penderita penyakit crohn - Nabila Noor Aisah; Yessi Crosita Octaria (Poltekkes Kemenkes Aceh, 2024)
Background: Crohn's disease patients experience dysbiosis or an imbalance in the composition of microbes in the gut, in contrast to individuals who do not have Crohn's disease. The intestinal immune system has a very important role in Crohn's disease. Pathogenesis can be understood from the immune system by knowing the gut microbiota. Short-chain fatty acids are anti-inflammatory substances produced from the breakdown of soluble fiber in the intestines by certain microbiota species.Objective: The purpose of this literature is to determine the effect of fiber on short-chain fatty acids and to form the gut microbiota of humans with Crohn's disease.Methods: Systematic searches were conducted on Google Scholar, PubMed, Science Direct and Scopus. Randomised controlled trials evaluating the role of fibre were sought between 2020-2024 to determine the application of fibre therapies and interventions to patients with Crohm's disease (age is not restricted).Results: This literature study revealed that fiber may affect the composition of gut microbiota diversity in patients with Crohn's disease. Fiber increases the gut microbiota and produces short-chain fatty acids, especially increasing Firmicutes, Bifidobacteria, and Roseburia bacteria in Crohn's disease patients. In intestinal cells, short-chain fatty acids undergo cell proliferation, cell differentiation and gene expression. Short-chain fatty acids function as ligands that pair with G-proteins (GPCRs), including GPR41, GPR43 so that they activate the anti-inflammatory signal cascade.Conclusion: A wide variety of fermented fibers are able to produce the diversity of the intestinal microbiota of Crohn's disease patients and produce short-chain fatty acid molecules that can activate anti-inflammatory signals. Therefore, fiber as a prebiotic is very beneficial in maintaining the intestinal immune system in Crohn's disease patients.